Praktik Pemenuhan Kewajiban Kelaiklautan Kapal Kargo Oleh Pengangkut Terhadap Ancaman Cyberattack - Stephen Wongso; Sinta Dewi Rosadi; Purnama Trisnamansyah; Fauzi Maulana Hakim (Universitas Widya Gama Malang, 2023)
Cyberattack issue in the shipping industries which was happened through some incidents towards ships, made the protection of cargo owners need to be reviewed. The seaworthiness obligation which interpreted as a means for a vessel to be fit to face the foreseeable perils in a voyage, makes cyberattack create its own discourse. This should not be separated with the cyberattack threat which has not been understood as an ordinary peril of a voyage. Moreover, the regulations in Indonesia which does not adopt the Hague-Visby Rules 1924, makes the industry fully rely on the Indonesian Shipping Law as a legal basis. The normative juridical research method makes the emphasis of the research on the use of library sources. The research specification uses an analytical descriptive that describes a literature study on the obligation of seaworthiness in dealing with the threat of cyberattack both in practice and regulation. The results of this study found that, first, the implementation of due diligence by the carrier in order to fulfil its seaworthiness obligations must also be applied to deal with the threat of cyberattack. The nature of the cyberattack that attacks the ship's information systems and technology, should make this attack predictable in a voyage. Moreover, the carrier's compliance with the cyber risk management guidelines on the ship should make the carrier declared to have fulfilled its seaworthiness obligations. Second, there is a legal vacuum in Indonesian positive law in regulating seaworthiness obligations in the face of cyberattack threats. Moreover, the legal gap between Indonesia's positive law and the 1924 HVR makes it difficult for Indonesian practitioners to follow global standards.